Analysis of genetic diversity among three Triplophysa tenuis populations by RAD-seq - Wu, Wenqiong; Qiu, Junqiang; Lin, Yue; Li, Xike; Li, Wenjuan; Duan, Yuanliang; Fu, Yuanshuai (Frontiers in Molecular Biosciences, 2024)
To investigate the genetic diversity of Triplophysa tenuis in the Shule River Basin of Gansu Province, three populations were sequenced using RAD-seq technology. Twenty-nine microsatellite (SSR) markers with polymorphisms were finally screened to access the genetic diversity among the populations, of which 15 had high polymorphisms. Quantity of the alleles detected in the three populations of T. tenuis varied from 2 to 24. The locus with the most alleles was SSRC1, which had 24 alleles. Among the 29 SSRs, the range of effective allele number, observed heterozygosity, expected heterozygosity, and polymorphic information content were 1.246 -16.615, 0.222 -1, 0.198 -0.940, and 0.178 -0.937, respectively. Most of the identified loci were in Hardy-Weinberg equilibrium. Analysis of population structure revealed that the Yumen and Changma populations shared the same origin while the Qiaowan population was different from them. The developed SSR markers discovered in this study will contribute to the conservation research of Triplophysa tenuis and the fishery resources conservation of the Shule River, providing scientific guidance for the development and utilization of Triplophysa tenuis resources and environmental protection.